Prognostic factors associated with achieving total oral diet following osteocutaneous microvascular free tissue transfer reconstruction of the oral cavity. (November 2019) - Kansara, Sagar; Wang, Tao; Koochakzadeh, Sina; Liou, Nelson E.; Graboyes, Evan M.; Skoner, Judith M.; Hornig, Joshua D.; Sandulache, Vlad C.; Day, Terry A.; Huang, Andrew T.
Highlights: In patients undergoing OMFTT, 57% achieve total oral diet. Those undergoing concurrent glossectomy have worse total oral diet achievement. N0/N1 stage and preop G tube independence are positive predictors of total oral diet achievement. Dental rehab and avoidance of postop fistula are positive predictors of total oral diet achievement. Abstract: Introduction: Osteocutaneous microvascular free tissue transfer (OMFTT) is the current standard in reconstruction of large bony defects of the oral cavity. Although being able to swallow ranks as a top priority for patients undergoing OMFTT, factors associated with achieving an oral diet following surgery remain unclear. We sought to describe the rate of total oral diet achievement, and to identify possible pre-, intra-, and post-operative factors associated with achievement in patients undergoing OMFTT. Methods: Retrospective review between January 1, 2010 and March 31, 2018 at two tertiary academic centers. Results: 249 patients (67% male, mean age 58 years) met inclusion criteria, with a median follow up of 15 months. Overall, 142 (57%) of patients achieved a total PO diet post-operatively, with median time to achievement of 3.2 months. Multivariate analysis identified that lack of concurrent glossectomy (SHR 1.72 [1.09–2.70], p = 0.02), N0/1 disease (SHR 1.92 [1.16–3.13], p = 0.011), avoidance of post-operative fistula formation (SHR 1.96 [1.22–3.23], p = 0.005), pre-operative G-tube independence (SHR 3.33 [1.69–6.25], p < 0.001), and successful dental rehabilitation (SHR 2.08 [1.43–3.03], p < 0.001) are independently associated with total oral diet achievement. Conclusions: Bony resections not requiring glossectomy, limited nodal disease burden, pre-operative gastrostomy-independence, avoidance of post-operative fistula, and dental rehabilitation are independently associated with achievement of total oral diet following OMFTT reconstruction of the oral cavity. Counseling patients on associated risk factors is important in guiding post-treatment expectations. Minimization of post-operative fistula, and maximization of dental rehabilitation may significantly improve total oral diet achievement in this patient population.